2018
DOI: 10.6061/clinics/2018/e473s
|View full text |Cite
|
Sign up to set email alerts
|

The human adrenal cortex: growth control and disorders

Abstract: This review summarizes key knowledge regarding the development, growth, and growth disorders of the adrenal cortex from a molecular perspective. The adrenal gland consists of two distinct regions: the cortex and the medulla. During embryological development and transition to the adult adrenal gland, the adrenal cortex acquires three different structural and functional zones. Significant progress has been made in understanding the signaling and molecules involved during adrenal cortex zonation. Equally signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 205 publications
(210 reference statements)
0
12
0
Order By: Relevance
“…The concept underlying the radiomics process is that both morphological and functional clinical images contain qualitative and quantitative information, which may reflect the underlying tissue-level features, in line with pathological findings (31). Previous studies have reported there were subtle structural and pathological differences between APA and CPA, which had different proportions composed of clear cells (lipid rich), compact cells (lipid poor), cell arrangement, and blood sinus, the same as previously discussed (23,24). APA cells contained mitochondria with lamellar-type or plate-like cristae, whereas CPA cells contained mitochondria with tubulovesicular cristae (24).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The concept underlying the radiomics process is that both morphological and functional clinical images contain qualitative and quantitative information, which may reflect the underlying tissue-level features, in line with pathological findings (31). Previous studies have reported there were subtle structural and pathological differences between APA and CPA, which had different proportions composed of clear cells (lipid rich), compact cells (lipid poor), cell arrangement, and blood sinus, the same as previously discussed (23,24). APA cells contained mitochondria with lamellar-type or plate-like cristae, whereas CPA cells contained mitochondria with tubulovesicular cristae (24).…”
Section: Discussionmentioning
confidence: 66%
“…The cells of the zona fasciculata and the zona glomerulosa of the adrenal cortex are responsible for producing cortisol and aldosterone, respectively. Histology shows that the zona fasciculata in the adrenal cortex occupies a larger area than zona glomerulosa; the former is the thickest zonas making up 50% of the cortex, and the latter accounts for around 15% of the thickness of the cortex (23). Next, the mean CT attenuation of CPA on precontrast CT image is higher than that of APA.…”
Section: Discussionmentioning
confidence: 95%
“…The adrenal glands consist of the outer connective tissue capsule, the cortex, and the medulla. The adrenal cortex and medulla have distinct embryologic and physiological functions [ 9 ]. The adrenal cortex is composed of three zones—the zona glomerulosa, zona fasciculata, and zona reticularis—which release mineralocorticoids, glucocorticoids, and androgens, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This is explained by the fact that during the embryonic period the cortex of the suprarenal glands is represented by an interrenal gland with non-differentiated cells (Barwick et al, 2005;El-Nahla et al, 2011;Xing et al, 2015). Formation of the zona glomerulosa and zona fasciculata (Sokolov, 1972;Kataoka, 1996;Lotfi et al, 2018) begins only in the second half of the embryonic development. A number of authors (Freedman et al, 2013;Pihlajoki et al, 2015) state that the cells of the zona glomerulosa can change and become cells of zona fasciculata.…”
Section: Discussionmentioning
confidence: 99%